Platelet Aggregation and Activation under Complex Patterns of Shear Stress - Zhang, Jian-ning; Bergeron, Angela L.; Yu, Qinghua; Sun, Carol; McIntire, Larry V.; López, José A.; Dong, Jing-fei (Thrombosis and Haemostasis, 2002)
Arterial stenosis results in a complex pattern of blood flow containing an extremely fast flow in the throat of stenosis and a post-stenosis low flow. The fast flow generates high shear stress that has been demonstrated in vitro to activate and aggregate platelets. One potential problem of these in vitro studies is that platelets are invariably exposed to a high shear stress for a period that is significantly longer than they would have experienced in vivo. More importantly, the role of the poststenosis low flow in platelet activation and aggregation has not been determined. By exposing platelets to a shear profile that contains both high and low shear segments, we found that platelets aggregate when they are exposed to a high shear stress of 100 dyn/cm2 for as short as 2.5 s, a period that is significantly shorter than those previously reported (30–120 s). Platelet aggregation under this condition requires a low shear exposure immediately after a high shear pulse, suggesting that post-stenosis low flow enhances platelet aggregation. Furthermore, platelet aggregation under this condition is not activation-dependent because the CD62P expression of sheared platelets is significantly less than that of platelets treated with ADP. Based on these findings, we propose that shear-induced platelet aggregation may be a process of mechanical crosslinking of platelets, requiring minimal platelet activation. This process may function as a protective mechanism to prevent in vivo irreversible platelet activation and aggregation under temporary high shear.
Keywords: Shear stress; stenosis; platelets activation; aggregation